Inter-temporal cost allocation and investment decisions - William P. Rogerson (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2007)
This paper considers the profit maximization problem of a firm that must make sunk investments in long-lived assets to produce output. It is shown that if per period accounting income is calculated using a simple and natural allocation rule for investment called the relative replacement cost (RRC) rule, that, in a broad range of plausible circumstances, the firm can choose the fully optimal sequence of investments over time simply by choosing a level of investment each period to maximize next period's accounting income. Furthermore, in a model where shareholders delegate the investment decision to a better-informed manager, it is shown that if accounting income based on the RRC allocation rule is used as a performance measure for the manager, robust incentives are created for the manager to choose the profit maximizing sequence of investments regardless of the manager's own personal discount rate or other aspects of the manager's personal preferences.
Older version: http://hdl.handle.net/10419/38694
Keywords: 330; Sunk Costs; Betriebswirtschaftliche Investitionstheorie; Reinvestition; Allokation; Theorie